Penerapan Analisis Common Size dalam Mengukur Perporma Keuangan Bank Syariah Indonesia Periode 2021-2024 - Yusuf Suleman; Selvi Selvi; Lanto Miriatin Amali (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the financial performance of Bank Syariah Indonesia through the Common Size method for the 2021–2024 period. The data collection technique used secondary data in the form of annual financial reports obtained from the official website published by the Indonesia Stock Exchange. The research employed a quantitative method since the data obtained were numerical. Data analysis was conducted by collecting, processing, and interpreting the data using the Common Size method, along with three financial ratios Profitability Ratio, Solvency Ratio, and Activity Ratio as tools to measure the company’s financial performance. The results indicate that the company’s financial performance, when analyzed using the Common Size method, was in a fairly good condition during the 2021–2024 period. From the asset side, there was an increase originating from the Musyarakah Financing account with a percentage of 23.11%, while the receivables account showed a decrease year by year, which is a positive sign for the bank. On the liabilities side, most components were fluctuating; however, the net income account in the income statement increased by 19.27% during the 2021–2024 period. Furthermore, the financial performance based on profitability ratios measured using the Net Interest Margin (NIM) and Operating Expense to Operating Income (BOPO) ratios was considered fairly good. The solvency ratio measured using the Debt to Asset Ratio was in good condition, while the Debt to Equity Ratio was considered less favorable. Meanwhile, the activity ratios namely accounts receivable turnover and working capital turnover were also deemed less satisfactory.